The Pattern of Information Structure in Junior High School Students in Informal and Formal Conversations - Rosmarie, Aprilia (Universitas Negeri Malang, 2020)
Since language as a communication tool, that’s why information structure is really important in language system and in the communication process. This research is aimed to find out the pattern of information structure in junior high school students, in one of junior high school in the private school in Semarang. The researcher focused on informal and conversations between student-student and teacher-student or student-teacher. The researcher got thirty six conversations of informal and formal conversations. This was a qualitative research and the researcher focused on Topic and Focus of each conversations, since topic and focus are important constructions in giving the information or constructing the sentence. As the result, in formal conversation, both of speakers (teacher or students) tended to eliminate the subject, or the TOPIC (47 percent), while only 33 percent of eliminating the predicate or the FOCUS, and the rest is only 20percent showed that there was no any elimination in the conversations. Meanwhile, in the informal conversation, both of speakers (teacher or students) tended to eliminate the subject, or the TOPIC (60percent), while only 27percent of eliminating the predicate or the FOCUS, and the rest is only 13percent showed that there was no any elimination in the conversations.